Distribution of new Staphylococcal Enterotoxin Genes (seg, seh, sei, sej, and sel) in Staphylococcus aureus Isolated from Retail Ready-to-Eat Foods in the Northeast Thailand - Khaenda, Bongkot; Namwat, Wises; Kotimanusvanij, Daroon; Chomvarin, Chariya (Srinagarind Medical Journal, 2016)
Background and Objective: Staphylococcus aureus is a common cause of food poisoning. Various ready-to-eat (RTE) foods have become increasingly popular in Thailand. The aim of this study was to investigate the distribution of enterotoxigenic S. aureus strains carring the newly important enterotoxin-encoding genes isolated from retail RTE foods in Khon Kaen municipality, Thailand. Methods: In this study, polymerase chain reaction (PCR) primers specific for the detection of newly staphylococcal enterotoxin (se); encoding genes including seg, seh, sei, sej and sel were used for the assay of 57 S. aureus isolates from 151 RTE food samples randomly collected from food vendors and food shops in Khon Kaen municipality that have been previously investigated for the five classical enterotoxin genes (sea-sed and tsst-1). Results: The result showed that the new enterotoxins could be found in 29.8% (17 of 57 isolates). The sea coexisted with seg was the most frequently found (12.3%), following by seg+sei (8.8%) and sec+seg (1.7%). Four isolates (7.0%) had single seg and none of S. aureus isolates had seh, sej and sel. Conclusion: These findings indicated that some new enterotoxin genes such as seg, and sei were the most frequently found and frequently coexists with other classical enterotoxin genes. Therefore, these new enterotoxins may play a role to cause food poisoning in RTE foods in Khon Kaen, Thailand.